Association between oral contraceptive use and markers of iron deficiency in a cross-sectional study of Tanzanian women. Issue 1 (January 2016) - Haile, Zelalem T.; Teweldeberhan, Asli K.; Chertok, Ilana R.A.
Abstract: Objective: To analyze the associations between oral contraceptive (OC) use and markers of iron deficiency, objectively measured using hemoglobin and soluble transferrin receptor. Methods: A secondary data analysis was performed of a population-based cross-sectional study using data from the 2010 Tanzania Demographic and Health Survey. Weighted percentages were calculated. Multivariable logistic regression was used to examine the associations between OC use and iron deficiency, anemia, and iron deficiency anemia. Results: Of the 4336 participants, only 7.3% reported a history of OC use. The prevalence rates of iron deficiency, anemia, and iron deficiency anemia were 30.3%, 40.9%, and 15.1%, respectively. Use of OCs was negatively associated with anemia and iron deficiency anemia, independent of potential confounders. Compared with OC nonusers, the multivariable-adjusted odds ratio among OC users was 0.44 (95% confidence interval 0.32–0.59; P  < 0.001) for anemia and 0.43 (95% confidence interval 0.27–0.68; P  < 0.001) for iron deficiency anemia. A longer duration of OC use was negatively associated with iron deficiency ( P  = 0.003 for trend), anemia ( P  < 0.001 for trend), and iron deficiency anemia ( P  < 0.001 for trend). Conclusion: The significant association between OC use and iron status has important implications for educating healthcare providers and women about additional nutritional benefits of the use of OCs.